Quality of life: Seasonal fluctuation in Parkinson's disease - Wu, Lei; Li, Shiyu; Tang, Yilin; Liang, Xiaoniu; Xu, Zhiheng; Hu, Tianyu; Liu, Xiaoli; Cai, Miao; Liu, Xuedong (Frontiers in Neurology, 2023)
Abstract Objective: Although the seasonal variation of motor and non-motor symptoms in Parkinson’s disease has been reported, association between seasonal changing and quality of life in patients with Parkinson’s disease remains to be explored. Methods: We recruited 1,036 PD patients in this cross-sectional retrospective study. Patients were divided into four groups based on their date of assessment according to the classical four seasons: group 1: March to May (n=241); group 2: June to August(n=259); group 3: September to November(n=273); group 4: December to February(n=263). The 39-item Parkinson’s Disease Questionnaire (PDQ-39) and other scales for other clinical evaluations scales for motor and non-motor symptoms were administered. The determinants of the quality of life (QoL) were analyzed by multiple stepwise regression analysis. Results: A significant difference of PDQ-39 was found between group 1 (spring months) and group 3 (autumn months) after correction (p=0.002). The Unified Parkinson’s Disease Rating Scale part III (UPDRS-III) score was higher in group 1 (spring months) than group 3 (the autumn months) (p=0.033). The most severe determinant of QoL was UPDRS-III score in group 1, and the Geriatric Depression Scale (GDS) score in group 2, group 3 and group 4. Interpretation: The current study reported seasonal fluctuation of QoL in PD patients, with higher scores during the spring months and lower scores in the autumn months. Since the determinants for QoL also vary by season, clinicians might need to focus on specific factors across seasons before initiating therapy.